MENGKAJI PR POLITIK: SEBUAH TINJAUAN TEORITIS DAN EMPIRIS - Indrayani, Inri Inggrit (Scriptura, 2014)
Political dynamics that is followed by a wave of democratization reinforcing the existence of the Public Relations (PR) as a ubiquitous entity. The interplay between Political PR with PR itself and Political Communication causes a misleading understanding about the domain of Political PR in the PR studies. Political PR is known as spin doctors refers to a negative perception, which emphasizes the model of PR propagandists rather than two way symmetrical communication. Although empirically, propagandist PR is still needed nevertheless the approach of two way symmetrical communication is more challenging that must be conducted by political actors in an account of democratization. This paper aims to convey a description about Political PR both theoretically and empirically as well as to distinguish Political PR and political communication. Political PR emphasises on the importance of relationship and management function in achieving political objectives instead of communicating political messages only as political communication do.